Dietary ketosis improves circadian dysfunction as well as motor symptoms in the BACHD mouse model of Huntington’s disease - Whittaker, Daniel S.; Tamai, T. Katherine; Bains, Raj S.; Villanueva, Sophia Anne Marie; Luk, Shu Hon Christopher; Dell’Angelica, Derek; Block, Gene D.; Ghiani, Cristina A.; Colwell, Christopher S. (Frontiers in Nutrition, 2022)
Disturbances in sleep/wake cycles are common among patients with neurodegenerative diseases including Huntington’s disease (HD) and represent an appealing target for chrono-nutrition- based interventions. In the present work, we sought to determine whether a low-carbohydrate, high-fat diet would ameliorate the symptoms and delay disease progression in the BACHD mouse model of HD. Adult WT and BACHD male mice were fed a normal or a ketogenic diet (KD) for three months. The KD evoked a robust rhythm in serum levels of β-hydroxybutyrate and dramatic changes in the microbiome of male WT and BACHD mice. NanoString analysis revealed transcriptional changes driven by the KD in the striatum of both WT and BACHD mice. Disturbances in sleep/wake cycles have been reported in mouse models of HD and are common among HD patients. Having established that the KD had effects on both the WT and mutant mice, we examined its impact on sleep/wake cycles. KD increased daytime sleep and improved the timing of sleep onset, while other sleep parameters were not altered. In addition, KD improved activity rhythms, including rhythmic power, and reduced inappropriate daytime activity and onset variability. Importantly, KD improved motor performance on the rotarod and challenging beam tests. It is worth emphasizing that HD is a genetically caused disease with no known cure. Life-style changes that not only improve the quality of life but also delay disease progression for HD patients are greatly needed. Our study demonstrates the therapeutic potential of diet-based treatment strategies in a pre-clinical model of HD.